Guidelines for Developing Multicultural Leadership in Primary School Teachers: A Case Study of the Pa Tueng Educational Quality Development Network Under the Chiang rai Primary Educational Service Area Office 3 - Jaipan, Waraporn; Tunkaew, Somkiet; Yawirach, Phoonchai (Academic Journal of MBU Lanna, 2025)
The objectives of this research were to: 1) study the current situation, desired conditions, and necessary requirements for developing cultural leadership qualities among elementary school teachers 2) investigate the factors contributing to the development of these qualities 3) propose development strategies. This research employed a research and development (R&D) approach. The study involved a targeted sample group of 125 individuals, including school administrators and elementary school teachers within an educational development network. Research methods included questionnaires, interviews, and group discussion recordings, with data analyzed using mean scores and standard deviations. The results of this research found that: The current and desired states for developing cultural leadership among elementary school teachers are highly favorable. Factors facilitating cultural leadership development include cultural knowledge, positive cultural attitudes, organizational relationship development, and openness to cultural diversity. Development strategies involve planning, policy setting, and clear management strategies aimed at enhancing teachers' cultural knowledge effectively and evaluating cultural attitudes to align with technological advancements to improve or adjust positive attitudes by leveraging a culturally diverse society in alignment with the development of multicultural leadership in a harmonious manner.